Diffusion of Anisotropic Particles in Random Energy Landscapes—An Experimental Study - Segovia-Gutiérrez, Juan Pablo; Escobedo-Sánchez, Manuel A.; Sarmiento-Gómez, Erick; Egelhaaf, Stefan U. (Frontiers in Physics, 2020)
If a colloidal particle is exposed to an external field, its Brownian motion is modified. In the case of an anisotropic particle, the external potential might not only affect its translation but also its rotation. We experimentally investigate the dynamics of a trimer, which consists of three spherical particles, within a random potential energy landscape. This energy landscape has energy values drawn from a Gamma distribution, a spatial correlation length similar to the particle size and is realised by a random light field, that is a laser speckle pattern. The particle translation and rotation are quantified by the mean squared (angular) displacement, the van Hove function and other observable quantities. The translation shows an intermediate subdiffusive regime and a long-time diffusion that slows down upon increasing the modulation of the potential. In contrast, the mean squared angular displacement exhibits only small deviations from a linear time dependence but a more detailed analysis reveals discrete angular jumps reflecting the symmetry of the trimer. A coupling between the translation and rotation is observed and found to depend on the length scale.